1980
DOI: 10.1111/j.1365-2141.1980.tb06015.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation Index: a Contribution to Quantification in the FAB Cla.ssification of Acute Leukaemia

Abstract: The French--American--British co-operative study group (FAB) criteria were used to classify acute leukaemia in 194 adult patients. The dividing lines between FAB subgroups M1--M2 and M5A--M5B appeared to be less well defined. In an effort to improve subtyping we introduce the maturation index (MI). (formula: see text). Clearly distinct subgroups emerged after arrangement of cases according to MI values. Immature and rather mature cases in both myeloblastic and monoblastic leukaemia were divided at a MI of 4%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] Only rarely have studies of bone marrow biopsies been reported,7' 72 except after chemotherapy. 73 With deepening understanding of the role of the marrow microenvironment in haematopoiesis, bone marrow biopsies in acute leukaemia will be reported more frequently.…”
Section: Normal Bone and Bone Marrowmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] Only rarely have studies of bone marrow biopsies been reported,7' 72 except after chemotherapy. 73 With deepening understanding of the role of the marrow microenvironment in haematopoiesis, bone marrow biopsies in acute leukaemia will be reported more frequently.…”
Section: Normal Bone and Bone Marrowmentioning
confidence: 99%
“…In several cases the changes were high enough to make assignment to another FAB-group mandatory. When the FAB-classification was quantified according to van Rhenen et a1 (2), this occurred in 5 out of 17 patients (29%). There appeared to be a tendency of lower MI's (<20) to rise and of higher MI's (>20) to decrease, both in myeloid and monocytoid groups.…”
Section: Resultsmentioning
confidence: 99%
“…Differential counting of 100 cells in the peripheral blood and 500 bone-marrow cells was carried out on coded smears, by two of us, on May-Griinwald-Giemsa stained smears made at presentation and at first or second relapse. The original FAB-criteria were used (l), as further quantified by van Rhenen et al (2).…”
Section: Methodsmentioning
confidence: 99%
“…Classification was done according to the FAB criteria, using cytochemical stains (Sudan black and a-naphtyl-acetate esterase) [13,14]. The degree of maturation was expressed as the maturation index (MI) [14].…”
Section: Fab Classification Maturation Index Peripheral Leukaemic Cmentioning
confidence: 99%